Perancangan Sistem Pembangkit Listrik Hybrid Tenaga Surya dan PLN - Yulisman Yulisman; Albeni Fakhri (Journal of Electrical Power Control and Automation (JEPCA), 2022)
Electrical energy is one of the most needed energy. The sun (sunlight) is a renewable energy that can be used to generate electrical energy. Indonesia is a tropical country, so there is quite a lot of sunlight available. In order to obtain efficient and safe (consistent) electrical energy, backup solar energy can be used with PLN's electrical energy using a hybrid system. The planned hybrid system uses 100 WP Poly-crystalline solar panels (2 pieces), 100 Ah 12 V batteries (2 pieces). The hybrid controller system uses a 1000 watt hybrid inverter. Applications that are designed to be used as labor lighting lamps (10 pieces) that require 1000 watts of power.